Petrological Studies of Yamato-74 Meteorites (1) - Yabuki, Hideo; Yagi, Kenzo; Onuma, Kosuke (1978)
P(論文) Chemical and petrologic classification of seven Yamato-74 meteorites was investigated in terms of microscopic observations and X-ray powder method. Yamato-74013 meteorite belongs to calcium-poor achondrite, diogenite with a granoblastic texture. Other six meteorites are ordinary chondrites. Recrystallization is fairly advanced in chondrites, except in Yamato-74191 meteorite which contains glassy material and clinohypersthene. Composition of olivine and orthopyroxene and petrographic observation indicate that Yamato-74014,-74080,-74094,-74191,-74362,and -74459 meteorites belong to H5,L6,H6,L3,L6 and H6 types of chondrite according to the classification of VAN SCHUMUS and WOOD (1967). departmental bulletin paper